Dristige damer i internasjonalt farvann - Isaksen, Lise Widding (Tidsskrift for kulturforskning, 2006)
Women On Waves (WOW) is an international feminist network organization working to expand and protect women’s reproductive rights. By using the Internet to fund and equip abortion ships sailing to international waters to give women from all countries legal and safe abortion services, they represent a new combination of feminist activism and vision. WOW organizes an abortion ship that visits local harbours in European countries like Ireland, Poland and Portugal where abortion is legally forbidden. WOW represents a new global health service that challenge the idea of abortion and reproductive rights as national issues. Local and global knowledge expert elites, sharing feminist visions and hopes to reduce women’s suffering and to improve the quality of motherhood all over the world, work together and illustrate new ways of combing global and local solidarities.